Colonization of Cutibacterium avidum during infant gut microbiota establishment. Issue 1 (1st November 2018) - Rocha Martin, Vanesa Natalin; Schwab, Clarissa; Krych, Lukasz; Voney, Evelyn; Geirnaert, Annelies; Braegger, Christian; Lacroix, Christophe
Abstract: Establishment of the infant gut microbiota affects gut maturation and influences long-term health. Cutibacterium (formerly Propionibacterium ) have been identified as early colonizers, but little is known about their function. Using a cultivation-dependent and -independent approach, we determined Cutibacterium prevalence, diversity and functional potential. In feces from a Swiss infant cohort (n = 38), prevalence of Propionibacterium/Cutibacterium decreased from 84% at 2 weeks, to 65% at 4 weeks, 47% at 8 weeks and 41% at 12 weeks of age. Abundance varied among individuals, and persistence depended on the colonization levels at 2 weeks. Cutibacterium isolates (n = 87) were obtained from 10 infants from a smaller cohort (n = 12); restriction fragment length polymorphism clustered isolates in four groups, and all identified as Cutibacterium avidum . Colonization potential and metabolic effects of C. avidum addition were tested in an in vitro continuous intestinal fermentation model mimicking infant proximal colon conditions. Cutibacterium avidum spiked daily at 10 8 or 10 9 cells mL −1 colonized, decreased formate and persisted during the washout period. Significant correlations were observed between Propionibacterium/Cutibacterium and lactate-producers and protein-degraders in both reactors and infant feces. Our findings highlight the natural presence of C. avidum and its role as a lactate-consumer and propionate-producer in infants younger than 3 months. Abstract : Abundance, persistence, diversity and functional impact of Cutibacterium in the infant gut.